Sarah Ridg Schuyler diary - Schuyler, Sarah Ridg.
Annotated typescript excerpts from a diary (1809 January 3-November 2) kept by Schuyler before her marriage, reflecting social life in Alexandria, Va., and Washington, D.C.
Typewritten transcript.
Born Sarah Ridg; married Anthony Day Schuyler.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Alexandria (Va.) -- Social life and customs; Virginia -- Social life and customs; Washington (D.C.) -- Social life and customs